Feminist and queer information studies reader - Keilty, Patrick; Dean, Rebecca, 1982- (Litwin Books series on gender and sexuality in information studies ;, 2013)
In Feminist and Queer Information Studies Reader, Keilty and Dean put the field of Information Studies into critical conversation with studies of gender, sexuality, race, and technology. In classic and original essays, renowned scholars from a range of disciplines think through a broad array of information and technology philosophies and practices. Conceiving of "information" in a broad sense, the contributors reevaluate conventional methods and topics within Information Studies to examine encounters with information phenomena and technology that do not lend themselves easily to the scientific and behaviorist modes of description that have long dominated the field. A Foreword, Introduction, and Afterword provide helpful context to the reader's 27 essays, arranged around topics that include information as gendered labor, cyborgs and cyberfeminism, online environments, information organization, information extraction and flow, archives, and performance.